STUDENT RESPONSES ON A LEARNING OF PARAGRAPH-BASED WRITING THROUGH CIRCLE THE SAGE BASED ON CRITICAL THINKING - testiana deni wijayatiningsih (Faculty of Humanities, Universitas Jenderal Soedirman, 2016)
Writing is one of English skills that students should master. There are some levels of writing described as follows: word-based writing, sentence-based writing, paragraph-based writing, genre-based writing and academic writing. Due to the above statements, students find it difficult to organize sentences into a coherent paragraph. Thus, the researcher conducts a research on analysis of student responses on a paragraph based writing course which uses a method of circle the sage based on critical thinking. This research uses a method of descriptive analysis. The data are collected using questionnaires to obtain the student responses on course learning of paragraph based writing through a method of circle the sage based on critical thinking. A descriptive-qualitative data analysis is used to analyze the learning achievement of a paragraph-based writing course through a method of circle the sage based on critical thinking. From the research results, it shows that lecturers are expected to use more applicable methods or techniques to enable students to have critical thinking to put their ideas in writing a paragraph